2014
DOI: 10.1186/1465-9921-15-63
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation state determines the response to rhinovirus infection in a mouse model of allergic asthma

Abstract: BackgroundThe mechanisms by which viruses cause asthma exacerbations are not precisely known. Previously, we showed that, in ovalbumin (OVA)-sensitized and -challenged mice with allergic airway inflammation, rhinovirus (RV) infection increases type 2 cytokine production from alternatively-activated (M2) airway macrophages, enhancing eosinophilic inflammation and airways hyperresponsiveness. In this paper, we tested the hypothesis that IL-4 signaling determines the state of macrophage activation and pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 67 publications
1
35
1
1
Order By: Relevance
“…Consistent with this, peripheral blood monocytes isolated from children undergoing viral-induced asthma exacerbations had elevated expression of alternatively activated macrophage signature genes (33). We have recently shown that, in the context of OVA sensitization and challenge, IL-4 receptor activation is required for M2 polarization of lung macrophages (34). Levels of the IL-4 receptor ligands IL-4 and IL-13 are likely to be enriched in the lungs of OVA-sensitized, RV-infected mice, consistent with intrapulmonary polarization.…”
Section: Original Researchsupporting
confidence: 62%
“…Consistent with this, peripheral blood monocytes isolated from children undergoing viral-induced asthma exacerbations had elevated expression of alternatively activated macrophage signature genes (33). We have recently shown that, in the context of OVA sensitization and challenge, IL-4 receptor activation is required for M2 polarization of lung macrophages (34). Levels of the IL-4 receptor ligands IL-4 and IL-13 are likely to be enriched in the lungs of OVA-sensitized, RV-infected mice, consistent with intrapulmonary polarization.…”
Section: Original Researchsupporting
confidence: 62%
“…Increased macrophage numbers have been occasionally reported in models of asthma exacerbation [33,35,36]. It has been shown that after rhinovirus infection, alternatively activated (M2) airway macrophages can release type 2 cytokines, particularly IL-13, contributing to a Th2-exacerbated phenotype [37,38]. However, in our model, IL-13 is not increased and does not seem to play a role in the exacerbation.…”
Section: Discussioncontrasting
confidence: 54%
“…The binding sites of STAT6 have been found in the target regions of a variety of IL-4-mediated genes, including CD23 (Cooper et al, 2012), IL-4R (Jenkins et al, 2013), eotaxin-1 (Waddell et al, 2013), eotaxin-3 (Nakayama et al, 2010), FIZZ1 (Dasgupta et al, 2011), and in Ig germline e (Lu et al, 2007) promoters. Recently, IL-4-driven STAT6 constitutive activation has been found in various diseases, such as allergy (Hong et al, 2014), tumors (Cheah et al, 2014;Creytens et al, in press;Koelsche et al, 2014), and lymphoproliferative disorders (Rawal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%